2021
DOI: 10.1007/s12325-021-01959-5
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Poly(ADP-Ribose) Polymerase Inhibitors in Ovarian Cancer: A Retrospective Cohort Study of US Healthcare Claims Data

Abstract: Introduction We aimed to characterize real-world utilization of poly(ADP-ribose) polymerase (PARP) inhibitors (PARPi) in women with ovarian cancer (OC). Methods This retrospective observational study of claims data from US MarketScan ® Commercial/Medicare Supplemental databases included women with OC initiating olaparib, niraparib, or rucaparib from January 1, 2017, to May 31, 2019. Patients were observed from first outpatient prescription unt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…A subsequent post hoc analysis reported that patients with a weight of less than 77 kg or a baseline platelet count of less than 150,000/mm 3 benefited from a reduced starting dose of 200 mg once daily (Berek et al, 2018) in the ENGOT-OV16/NOVA study. In a retrospective cohort study of US health care claims data, fewer patients receiving niraparib (69.3%) than olaparib (89.4%) or rucaparib (93.2%) started treatment at the highest indicated dose (Arend et al, 2021). The above results suggest that modified niraparib doses were implemented in clinical practice to mitigate the risk of severe hematologic toxicity.…”
Section: Hematologic Toxicitymentioning
confidence: 96%
“…A subsequent post hoc analysis reported that patients with a weight of less than 77 kg or a baseline platelet count of less than 150,000/mm 3 benefited from a reduced starting dose of 200 mg once daily (Berek et al, 2018) in the ENGOT-OV16/NOVA study. In a retrospective cohort study of US health care claims data, fewer patients receiving niraparib (69.3%) than olaparib (89.4%) or rucaparib (93.2%) started treatment at the highest indicated dose (Arend et al, 2021). The above results suggest that modified niraparib doses were implemented in clinical practice to mitigate the risk of severe hematologic toxicity.…”
Section: Hematologic Toxicitymentioning
confidence: 96%
“…79 The IQVIA Institute for Human Data Science estimates global spending on oncology drugs will reach $269 billion by 2025. 80 Specifi cally, in the United States, IQVIA highlights MM because annual spending has increased 20% or more since 2017. This increase refl ects the arrival of new treatment options to the market with novel mechanisms of action, improved diagnosis rates, and longer treatment durations.…”
Section: Managed Care Considerations Economic Burden Of Multiple Myelomamentioning
confidence: 99%
“…This increase refl ects the arrival of new treatment options to the market with novel mechanisms of action, improved diagnosis rates, and longer treatment durations. 80 The National Cancer Institute's Physician Data Query cancer information summary about fi nancial toxicity and cancer treatment states, "fi nancial toxicity and fi nancial distress are used to describe how out-of-pocket costs can cause fi nancial problems for a patient." 81 Patients who have MM are at a higher risk of fi nancial toxicity, as they are likely to develop advanced-stage cancer, recurrent cancer, and cancer with a poor prognosis.…”
Section: Managed Care Considerations Economic Burden Of Multiple Myelomamentioning
confidence: 99%
See 2 more Smart Citations